Natar Sori Sebagai Sumber Belajar Sejarah Lokal - Payara, Paulina; Kubangun, Nur Aida; Far-Far, Gazali (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2022)
Natar Sori, in the village of Arui Das, Wertamrian District, Tanimbar Islands Regency, serves as a source for local history learning. Natar Sori facilitates the development of local historical awareness, particularly among students and the younger generation in the village. The issues to be explored in this paper are: 1) What is the history behind the establishment of Natar Sori as a cultural heritage object and historical site by the ancestors of the Arui Das community? 2) How is the cultural heritage of Natar Sori utilized as a source for local history learning in Arui Das village, Wertamrian District, Tanimbar Islands Regency? 3) What is the function of Natar Sori in addressing the interests or issues present in the village of Arui Das? As a cultural heritage object, the Natar Sori site needs to be preserved as it is an important part of the Cultural Heritage Law that ensures the preservation of cultural heritage objects within the community. This site can also be used as a source of local history learning in schools on Yamdena Island, enabling the transfer of knowledge to future generations so that they do not forget their history, which is a fundamental part of a nation's identity.